Pengaruh Laba Terhadap Harga Saham Serta Kebijakan Dividen Sebagai Variabel Intervening Perusahaan Teknologi Yang Terdaftar di Bursa Efek Indonesia - Cici Widya Prasetyandari (Manivest : Jurnal Manajemen, Ekonomi, Kewirausahaan, dan Investasi, 2024)
Technology companies are companies that have great potential to develop their business. The reason is that the 4.0 era is an era where technology is developing very rapidly. The aim of this research is to understand the role of dividend policy as an intervention between profits and share prices. The population of this research is all technology companies listed on the IDX in the 2017-2022 period. The sample selection method uses a purposive sampling method. The research method used is path analysis. The research results show that dividend policy does not act as an intervening variable between profits and share prices. Profit and dividend policy have no effect on share prices. Profit also has no effect on the dividend policy of technology companies.